1978
DOI: 10.1111/j.1348-0421.1978.tb00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the Physiological Role of Autolysis by a Comparative Study with a Wild‐Type and its Non‐Autolytic Mutant of Micrococcus lysodeikticus (luteus) Cultivated with Externally Added Proteolytic Enzymes*

Abstract: The log phase cells of autolytic Micrococcus lysodeikticus (luteus) IFO 3333 did not autolyze when grown in the presence of trypsin although the growth curve and morphology of the cells were not influenced.A non-autolytic mutant was obtained by subculture of the wild-type strain IFO 3333 on an agar slant containing 1% glucose. The mutant (strain MT) was arranged in tetrads or in clusters consisting of regular tetrads, in contrast to the wild-type IFO 3333 which occurred singly or in irregular masses. The mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
2

Year Published

1978
1978
2001
2001

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 34 publications
(7 reference statements)
1
22
2
Order By: Relevance
“…Bergey's Manual (8th ed.) notes that M. lysodeikticus has no visible capsule, and we have not so far discerned any capsule-like material around individual cells, as reported previously (17). However, the present study has revealed that the bridge formed by the fluffy materials and a small void space at the junction of the cross wall with peripheral wall were observed in thin sections of wild-type IFO 3333 cells (Fig.…”
Section: Resultscontrasting
confidence: 33%
See 4 more Smart Citations
“…Bergey's Manual (8th ed.) notes that M. lysodeikticus has no visible capsule, and we have not so far discerned any capsule-like material around individual cells, as reported previously (17). However, the present study has revealed that the bridge formed by the fluffy materials and a small void space at the junction of the cross wall with peripheral wall were observed in thin sections of wild-type IFO 3333 cells (Fig.…”
Section: Resultscontrasting
confidence: 33%
“…When grown in the liquid medium with proteolytic enzymes added, the mutant tetrads form cell packets arranged regularly in three dimensions (17). Figure lab shows thin sections of the trypsin-induced cell packets.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations